Enzybiotics LYSSTAPH-S and LYSDERM-S as Potential Therapeutic Agents for Chronic MRSA Wound Infections - Lukáš Vacek; Šárka Kobzová; Richard Čmelík; Roman Pantůček; Lubomír Janda (MDPI AG, 2020)
Antibacterial antibiotic therapy has played an important role in the treatment of bacterial infections for almost a century. The increasing resistance of pathogenic bacteria to antibiotics leads to an attempt to use previously neglected antibacterial therapies. Here we provide information on the two recombinantly modified antistaphylococcal enzymes derived from lysostaphin (LYSSTAPH-S) and endolysin (LYSDERM-S) derived from kayvirus 812F1 whose target sites reside in the bacterial cell wall. LYSSTAPH-S showed a stable antimicrobial effect over 24-h testing, even in concentrations lower than 1 µg/mL across a wide variety of epidemiologically important sequence types (STs) of methicillin-resistant Staphylococcus aureus (MRSA), especially in the stationary phase of growth (status comparable to chronic infections). LYSDERM-S showed a less potent antimicrobial effect that lasted only a few hours at concentrations of 15 μg/mL and higher. Our data indicate that these antimicrobial enzymes could be of substantial help in the treatment of chronic MRSA wound infections.